Cycles of Needs and Wants: Entrepreneurial Journalism in Pakistan - Saeed, Muzammil; Khan, Aruna; Rasool , Farasat (Journal of Peace, Development and Communication, 2021)
Technological convergence in the “global village” of today has created an opportunity for journalists to navigate through the consequential media convergence and create their individual space in the market economy. New digital technology helps individuals to produce and broadcast different types of content encouraging varieties of entrepreneurial journalism. This study aims to explore the reasons and practices of digital entrepreneurial journalism in Pakistan and the role of mobile media technology in this new scenario. For this purpose, we conducted interviews of 30 entrepreneurs who are running their YouTube news channels. It was revealed that the layoffs of journalists from the media industry along with the filtering and priming of news by media conglomerates contributed to journalists looking for alternatives. Digital information technology provides an effective alternative for journalists to disseminate information creating a pathway for entrepreneurial journalism. Data collected about the role of smartphone technology disclosed that media convergence has made smartphones a primary and affordable means to reach the singular mega platform for information dissemination. Various smart applications provide economical broadcasting techniques to reach multiple online platforms. Although technology provides an opportunistic perspective to entrepreneurial journalism, this research further exposes entrepreneurial journalism as an emerging need of Pakistani journalism rather than just an opportunity due to the possession of freedom of expression and economic independence.